ZNF516 suppresses EGFR by targeting the CtBP/LSD1/CoREST complex to chromatin - Lifang Li; Xinhua Liu; Lin He; Jianguo Yang; Fei Pei; Wanjin Li; Shumeng Liu; Zhe Chen; Guojia Xie; Bosen Xu; Xia Ting; Zihan Zhang; et al. (Nature Communications, 2017)
EGFR is a well-known oncogene; however, the mechanisms regulating its expression are still unclear. Here, analysing genome-wide chromatin associations, the authors show that in breast cancer cells ZNF516 represses EGFR transcription through the interaction with the CtBP/LSD1/CoREST complex.